Corneal Endothelial Cell Loss after Vitrectomy with Silicone Oil Tamponade in Phakic Versus Pseudophakic Patients with Rhegmatogenous Retinal Detachment - Shaheer, Muhammad; Khan, Asad Aslam; Ahmed, Nasir; Mahju, Tehseen Mahmood; Rasheed, Ummara (Pakistan Journal of Ophthalmology, 2017)
Purpose: To evaluate the corneal endothelial cell loss in patients of rhegmatogenous retinal detachment after vitrectomy with silicone oil tamponade. Study Design: Randomized control study. Place and Duration of Study: Eye Unit-III, Institute of Ophthalmology, Mayo Hospital, Lahore. 1st May 2016 to 30 April 2017. Material and Methods: 50 patients were selected from the outpatient department of Institute of Ophthalmology, Mayo hospital who were diagnosed with rhegmatogenous retinal detachment. They were divided into two groups A and B. Group A included 25 patients who were phakic in the involved eye while group B contained 25 patients who were pseudophakic in the involved eye. The fellow eyes of all the patients were phakic. Patients diagnosed with Tractional retinal detachment, combined Tractional & rhegmatogenous retinal detachment, any coexisting corneal or retinal disease and those having history of ocular surgery other than cataract surgery were excluded from study. All the patients underwent 23 gauge pars plana vitrectomy with silicone oil tamponade. All patients underwent pre-operative and three months post-operative bilateral specular microscopy for endothelial cell count, percentage of hexagonal cells and coefficient of variation. Specular microscopy was done by researcher and findings were recorded. Results: The endothelial cell count was decreased in both the groups showing a cell loss of 30.48 ± 25.78 in phakic patients group and 77.52 ± 40.03 in pseudophakic patients group. The decrease in the endothelial cell count was statistically insignificant. Conclusion: Vitreo retinal surgery with silicone oil tamponade decreases endothelial cell count and it may affect the corneal anatomy in the long run and affect visual prognosis. Key words: Rhegmatogenous retinal detachment, Specular microscope, Corneal endothelial cell count, Phakic, Pseudophakic.